Artificial Light at Night Alters the Physiology and Behavior of Western Mosquitofish (Gambusia affinis) - Miner, Krystie A.; Huertas, Mar; Aspbury, Andrea S.; Gabor, Caitlin R. (Frontiers in Ecology and Evolution, 2021)
Human population growth and its associated effects on the environment contribute to the rapid decrease of biodiversity worldwide. Artificial light at night (ALAN) is an anthropogenic pollutant that is increasing with the spread of urbanization and may contribute to biodiversity declines. ALAN alters the migration patterns of birds, communication in frogs, and impacts reproduction, behavior, and physiology of multiple other taxa. However, most of the studies on ALAN are based on terrestrial systems, and overall, the effects of ALAN on freshwater organisms are poorly understood. We investigated how ALAN affects the physiology, behavior, and reproduction of a widespread, tolerant species of freshwater fish. Gambusia affinis are small livebearing fish often found in urban streams. We exposed groups of female G. affinis to either a natural light cycle or a constant 24-hour light cycle (ALAN) in the laboratory for 60 days. In another experiment, we exposed female G. affinis to the same treatments in outdoor mesocosms for 32 days. We found that exposure to ALAN lowered glucose levels in the brain and decreased swimming activity, but had no effect on cortisol release rates, reproduction, survival, or growth. This research is strengthened by measuring multiple metrics in response to ALAN and by incorporating both a field and laboratory component which confirm similar results. These results suggest that this tolerant species of fish may behaviorally adjust to ALAN rather than modulate their endocrine stress response.